A note on the Boardman theorem - Zhi Lü; Chun-Lian Zhou (International Journal of Mathematics and Mathematical Sciences)
Let (T,Mn) be a smooth involution on a closed n-dimensional manifold with n≤52dimF. This paper gives three necessary and sufficient conditions that (T,Mn) is a bounding involution.